The Effect of Village Original Income, Village Allocation of Funds, Tax Sharing and Retribution on Village Expenditures - Ilma Dwi Amaliah (SMART Insight, 2022)
The purpose of this study was to determine the magnitude of the influence of Village Original Income, Village Fund Allocation, Tax Sharing and Retribution on Village Expenditures in Villages in Parungponteng District, Cibalong District and Sukaraja District, Tasikmalaya Regency in 2018-2021. The research method used is quantitative with a case study approach and data analysis techniques using panel data regression. The sample selection used purposive sampling and obtained a sample of 11 villages. The results of the study show that (1) Village Original Income Village Original Income fluctuates. The allocation of Village Funds has increased, but initially experienced a significant decrease. Profit Sharing Taxes and Levies experienced an increase but also experienced a significant decrease. Village spending has increased value. (2) Partially Original Village Income has a significant positive effect on Village Expenditure, Village Fund Allocation has a significant positive effect on Village Expenditures, Tax and Retribution Revenue Sharing has a significant positive effect on Village Expenditure, and simultaneously Effect of Village Original Income, Village Fund Allocation, Distribution The results of taxes and levies have a significant positive effect on village spending.